Educational Quality and Innovation (Cultura Económica, 2018)
In educational discourse there is a tendency to seek "magical" solutions. Analogously, in certain discourses of social reform it is stated that education has the magic bullet to solve all the problems of society. The article starts with a quote by Borges that can be applied to the contemporary notion of innovation or educational quality. The Argentine writer cites the famous idola fori by Francis Bacon in the epilogue to the book Historia de la Noche (1977). There, he describes them as worn words that do not leave a lot to do with them. Based on this intuition, this article proposes the limits of the notions of innovation or educational quality and the circular recurrence in education to concepts that act as salvific narratives. The article proposes an inverse way to explore educational quality and innovation: an inductive path that identifies spaces or transformation processes in and from schools.
Keywords: EDUCATION; QUALITY; INNOVATION; TEACHERS; SALVIFIC NARRATIVES